Novel Therapeutics for Ovarian Cancer: The 11th Biennial Rivkin Center Ovarian Cancer Research Symposium. (1st November 2017) - Johnson, Neil; Liao, John B.
Abstract : Objective: The aim of this study was to summarize developments in novel therapeutics for ovarian cancer presented at the Ovarian Cancer Research Symposium held at the University of Washington. Methods: A symposium of the leaders in ovarian cancer research was convened to present and discuss current advances and future directions in ovarian cancer research. Results: The fourth session was held on September 13, 2016, and focused on Novel Therapeutics for Ovarian Cancer. The session featured a keynote presentation on Novel Immunotherapeutics for Ovarian Cancer from Nora Disis and an invited oral presentation from Scott Kaufmann that discussed poly (ADP-ribose) polymerase (PARP) Inhibitor Combinations for the Treatment of Ovarian Cancer. Eight additional oral presentations were selected from abstract submissions. Thirty-eight abstracts were presented as posters highlighting recent advances in tumor immunology, PARP inhibition, chemoresistance, and novel targets for ovarian cancer therapy. Conclusions: PARP inhibitors, immunotherapies, and targeted therapies are but some of the expanding number of treatment options for ovarian cancer patients. Identification of the subsets of patients who will benefit most from these treatments remains the subject of intense preclinical and clinical research. Evidence presented at this symposium suggests that non-BRCA patients also benefit from PARP inhibitor therapies. Improved understanding of the mechanisms of chemoresistance and encouraging preclinical data presented for combinatorial approaches may soon yield new therapies for ovarian cancers that are resistant and refractory to standard treatments.